The Role Of Intelligence In E-Learning Usage: An Extension Of Utaut Model - Panjaitan, Erwin Setiawan (2019)
The main aim of this research is to ascertain the moderating role of intelligence and determine the mediating role of behavioural intention on the use of E-learning among third year Indonesian undergraduates. Specifically, by conducting survey in Indonesia, it covering 360 respondents among third year Indonesia undergraduates. This thesis examines the accuracy of Unified Theory of Acceptance and Use of Technology (UTAUT) and it is moderated by the intelligence level of users. The main contribution from this research is introducing intelligence level on UTAUT model to reveal the role of cognitive process level on an acceptance and usage of new technology. Our mediator results show that Performance Expectancy and Effort Expectancy are no mediation, Facilitating condition and EQ are partial mediation with competitive and IQ and social influence are fully mediation. All the model have larger moderating effect to use behaviour of E-learning among Indonesia third year undergraduates. However, the finding for the moderator result shows significant moderator influence in terms of social influence only. This research implies the three important findings for the policy makers. First, policy maker should provide the e-learning to undergraduate student in Indonesia such as communicate, shared knowledge, teamwork and cooperation. Second, policy maker can explains that the important of social influence is a strong promoter for students to use blogs in their e-business learning and teaching. Last but not least, policy maker (school board; government)should more focus on social influence to use e-learning because it is able to attract the student’s awareness and attention.